Enfermedades culturales de Taxco, México. - Urióstegui-Flores, Adrián (Revista de Salud Pública)
Objective Record A) the cultural illnesses of Taxco de Alarcón, as well as B) the causes and treatments of said illnesses. Material and Methods The research is qualitative, non-probabilistic. Documentary research, key informants, focus groups and in-depth interviews were used. The work was carried out in the city of Taxco de Alarcón, located in the estado de Guerrero, in México. Results 36 cultural diseases were recorded. Conclusions As confirmed, the population interviewed continues to deal with various cultural diseases on a daily basis, which are part of a valid and current traditional medical worldview.